Quercetin, Luteolin, and Epigallocatechin Gallate Promote Glucose Disposal in Adipocytes with Regulation of AMP-Activated Kinase and/or Sirtuin 1 Activity - Xiao, Na; Mei, Fan; Sun, Yan; Pan, Guojun; Liu, Baolin; Liu, Kang (Planta Medica, 2014)
Quercetin, luteolin, and epigallocatechin gallate are flavonoids abundant in edible and medicinal plants with beneficial effects on glucose homeostasis. This study explored the action of these flavonoids on glucose disposal in adipocytes. Quercetin, luteolin, and epigallocatechin gallate enhanced glucose consumption with the positive regulation of AMP-activated kinase phosphorylation, and the AMP-activated kinase inhibitor compound C abolished their effects on glucose consumption. Luteolin and epigallocatechin gallate, but not quercetin, increased sirtuin 1 abundance, and their regulation of glucose consumption was also attenuated by co-treatment with sirtuin 1 inhibitor nicotinamide. Quercetin, luteolin, and epigallocatechin gallate suppressed nuclear factor-κB activation by inhibition of p65 phosphorylation with beneficial regulation of adipokine expression, whereas these actions were diminished by coincubation with compound C. The sirtuin 1 inhibitor nicotinamide attenuated the effects of luteolin and EGCG on p65 phosphorylation and adipokine expression without any influence on the activity of quercetin. Results of Western blot and fluorescence microscopy also showed that quercetin, luteolin, and epigallocatechin gallate increased Akt substrate of 160 kDa phosphorylation and promoted 2-deoxy-D-glucose uptake by adipocytes under basal and inflammatory conditions. These findings suggested that quercetin, luteolin, and epigallocatechin gallate inhibited inflammation and promoted glucose disposal in adipocytes with the regulation of AMP-activated kinase and/or sirtuin 1.
Keywords: flavonoids; AMPK; SIRT1; glucose disposal; adipocytes